To find the constant of variation, we can use the relationship given in the problem. We know that the weight of the object on Earth (W_E) varies directly with its weight on the moon (W_M).
The formula for direct variation can be expressed as:
\[ W_E = k \cdot W_M \]
where \( k \) is the constant of variation.
Given that:
- \( W_E = 300 \) pounds (weight on Earth)
- \( W_M = 48 \) pounds (weight on the moon)
We can substitute these values into the equation to solve for \( k \):
\[ 300 = k \cdot 48 \]
Now, we rearrange the equation to solve for \( k \):
\[ k = \frac{300}{48} \]
Calculating this gives:
\[ k = 6.25 \]
So, the constant of variation is \( \boxed{6.25} \).